2011
DOI: 10.1016/j.molimm.2011.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the TREM-1/DAP12 pathway in the innate immune responses to Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis, is a Gram-negative obligate oral anaerobic bacterium highly implicated in periodontal disease, the most prevalent chronic inflammatory disease, but recent evidence also indicates a potential contribution to systemic inflammation. The Triggering Receptor Expressed on Myeloid cells 1 (TREM-1) is a cell surface receptor of the immunoglobulin superfamily, which, along with its adaptor signalling molecule DAP12, is involved in immune response to bacterial and fungal infections, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
62
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(78 citation statements)
references
References 70 publications
16
62
0
Order By: Relevance
“…and in vitro models by agonist monoclonal antibodies further stimulates the production of pro-inflammatory cytokines (Bleharski et al, 2003;Bostanci et al, 2011;Bouchon et al, 2001;Radsak et al, 2004). A synergism exists between the activation of TREM-1 and toll-like receptors or Nod-like receptors, resulting in amplification of pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and inhibition of anti-inflammatory cytokines such as IL-10 (Bleharski et al, 2003).…”
Section: The Engagement Of Trem-1 In In Vivomentioning
confidence: 99%
“…and in vitro models by agonist monoclonal antibodies further stimulates the production of pro-inflammatory cytokines (Bleharski et al, 2003;Bostanci et al, 2011;Bouchon et al, 2001;Radsak et al, 2004). A synergism exists between the activation of TREM-1 and toll-like receptors or Nod-like receptors, resulting in amplification of pro-inflammatory cytokines, including tumor necrosis factor (TNF)-α, interleukin (IL)-1β, and inhibition of anti-inflammatory cytokines such as IL-10 (Bleharski et al, 2003).…”
Section: The Engagement Of Trem-1 In In Vivomentioning
confidence: 99%
“…TLR-induced signals (especially TLR-2) are amplified by activated TREM-I leading specifically to an increase in cytokine (IL-1α, TNF-α, Granulocyte-macrophage colony-stimulating factor (GM-CSF)) and chemokine (IL-8, Monocyte chemotactic protein 1 (MCP-1), MCP-3, Macrophage Inflammatory Proteins (MIP-1) production [27]. Blocking TREM-1 decreases Th1 signaling through IL-1β, Interferon (IFN)-γ, and IL-6 and increases Th2 production of IL-4, IL-5, and IL-10 [8, 28, 29]. Toll-like Receptors (TLRs) are germ line encoded receptors of the innate immune response responsible for distinguishing between microorganisms and responding appropriately to specific microbes [30].…”
Section: Triggering Receptor Expressed On Myeloid Cells (Trem)-1mentioning
confidence: 99%
“…Upon recognition of bacterial challenge by TLRs and PAMPs, TREM-1/DAP12 interactions mediate downstream signaling to increase proinflammatory cytokine production [27]. Research conducted by Bostanci et al [8] revealed P. gingivalis can disrupt the TREM-1/DAP12 signaling pathway. Through this mechanism, P. gingivalis was determined to have engagement with TREM-1 and may act to regulate systemic inflammation [8].…”
Section: Triggering Receptor Expressed On Myeloid Cells (Trem)-1mentioning
confidence: 99%
See 2 more Smart Citations